STRATEGY AND SUCCESS OF INDONESIAN TELEVISION JOURNALISTS ASSOCIATION (IJTI) LAMPUNG IN ISLAMIC COMMUNITY DEVELOPMENT ACTIVITIES - Dewi Puspitasari; Hasan Mukmin; Fariza Makmun; Fitri Yanti (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
Television (TV) can be a good means of education and coaching. Various messages of kindness can be broadcast on TV so that they can help Islamic community development activities through Islamic studies on TV shows. The broadcast process cannot be separated from the role of journalist organizations, such as in Bandar Lampung through the Indonesian Television Journalists Association (IJTI) Lampung. The problem in this study is how the strategy and success of IJTI Lampung in carrying out Islamic community development activities. The research in this thesis uses qualitative descriptive methods, in the process of finding and compiling the data is carried out systematically using field data, documentation or notes obtained by the author. Then the author of which groups are important and which will be studied to make conclusions and can be made an objective decision. The results showed that the strategy carried out by IJTI Lampung in the development of Islamic society was in accordance and could be said to be successful with organizational strategy theory, where the actions taken were to conduct journalistic training, participate in monitoring in the field, and evaluate the results of training to the community, especially students. In addition, the strategy carried out is in accordance with the theory of community development where the trainees are given maximum debriefing with the aim of being able to develop their potential d ßan ability in the field of journalism.